Estudo de Impurezas de Carbono em Nanoestruturas de BN - Gonçalves, Rebeca Dourado (2008)
In this work, we performed an analysis of the structural and electronic stability of nanostructures of Boron Nitride (BN), such as layers, tubes and cones, when doped with Carbon, through first-principles calculations as implemented in code SIESTA. We found that substitutional doping of Carbon for either a single Boron or a single Nitrogen atom produces significant changes in the conductive properties of each material. Such replacement process transforms the formerly insulating material, in a n-type conductor, donnor of electrons, for Boron replaced by Carbon, and the p-type, acceptor of electrons, for the Nitrogen substitution. Furthermore, we also performed calculations with spin-polarization and found occurrence of spontaneous magnetization of 1μB for all doped structures, except for tube (6,0), which presented a magnetic moment of 0;2μB. This magnetization is attributed to the unpaired electron located in the pz orbital of carbon. It was also noted that the doped layers become more energetically stable as the number of atoms increases. To the tubes, increased stability occurs with the increase in diameter combined with the consequent increase in the number of atoms. At the cones, stability energy is reduced with the increase in the angle of disclination. These effects are the result of a combination of percentage concentration of the defect and the greater or lesser degree of hybridization.